2013
DOI: 10.1002/cphc.201300711
|View full text |Cite
|
Sign up to set email alerts
|

The Lateral and Axial Localization Uncertainty in Super‐Resolution Light Microscopy

Abstract: A study of the uncertainty of localizing single-molecule emitters for super-resolution light microscopy is presented. Maximum likelihood estimation (MLE) is found to be superior to least-squares fitting for low background levels, but the performance difference between the two methods decreases to a few percent for practical background levels. It is shown that the performance limit of MLE, the Cramér-Rao lower bound, is well described by a concise analytical formula with only spot width and signal and backgroun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
131
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(136 citation statements)
references
References 39 publications
(64 reference statements)
0
131
0
Order By: Relevance
“…Selecting the five best algorithms, we found that the accuracies are 21.05 nm and 32.13 nm for LS1 and LS2, respectively. They are worse than predicted by Thompson 20 .…”
Section: Evaluation and Scoring Calculation Theoretical Accuracymentioning
confidence: 59%
See 1 more Smart Citation
“…Selecting the five best algorithms, we found that the accuracies are 21.05 nm and 32.13 nm for LS1 and LS2, respectively. They are worse than predicted by Thompson 20 .…”
Section: Evaluation and Scoring Calculation Theoretical Accuracymentioning
confidence: 59%
“…There also exist refined CRLBs that take pixelation, various sources of noise, and fluorescence background into account. A survey of localization accuracy and precision in the SMLM context can be found in Deschout et al 64 , while uncertainties in the lateral localization in super-resolution microscopy were also addressed in Rieger et al 20 .…”
Section: Evaluation and Scoring Calculation Theoretical Accuracymentioning
confidence: 99%
“…Here, N l is the total number of photons, ðx l ; y l Þ is the fluorophore position, ands l is the effective width of the PSF. The latter accounts for the finite pixel size a  a and is related to the true Gaussian width s by the relations 2 ¼ s 2 þ a 2 =12 (15,16,19,20). Analytical CRLBs for parameter errors are calculated by inserting this PSF model into Eq.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in spot footprint is comparable to the different methods for 3D-localization [12]. These predictions are tested with simulations, using realistically simulated spot shapes including effects of vector diffraction [13] and of a finite spectral emission bandwidth (Gaussian shape, FWHM 35 nm).…”
mentioning
confidence: 90%
“…The precision for finding the center positions of the different orders is Δx j σ a ∕ N j 1 − I 1 τ j p , and the precision for finding the photon counts for each diffraction order is ΔN j N j ∕1 − I 0 τ j p , with the functions I n τ τ∕n! R ∞ 0 dtt n ∕1 τe t of the dimensionless background parameter τ j 2πσ 2 a b∕N j a 2 , where σ 2 a σ 2 a 2 ∕12 [11,12]. A Cramér-Rao lower bound (CRLB) analysis gives the best possible estimate for the emitter position and the wavelength as:…”
mentioning
confidence: 99%